1983
DOI: 10.1590/s0074-02761983000300005
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive isolation between different forms of Lutzomyia longipalpis (Lutz & Neiva), (Diptera: Psychodidae), the vector of Leishmania donovani chagasi Cunha & Chagas and its significance to kala-azar distribution in South America

Abstract: The males of the sandfly Lutzomyia longipalpis occur in two forms, one which bears a single pair of pale spots on tergite 4 and another in which an additional pair of spots characterizes tergite 3. In crosses between laboratory reared stocks of the two forms originating from allopatric and sympatric sites in Brazil nearly all males of one form fail to inseminate females of the other. In addition, insemination failure between some allopatric populaytions of Lu. longipalpis with similar tergal spot patterns is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
105
2
7

Year Published

1987
1987
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(124 citation statements)
references
References 0 publications
10
105
2
7
Order By: Relevance
“…As before, all females that were mated to homospecific males, and that did not die before laying eggs, successfully produced larvae. Similar results were obtained by Ward et al (1983Ward et al ( , 1988) who observed insemination failure in copulations between males and females of some Brazilian populations, including the Sobral siblings. Interestingly enough, Lu.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…As before, all females that were mated to homospecific males, and that did not die before laying eggs, successfully produced larvae. Similar results were obtained by Ward et al (1983Ward et al ( , 1988) who observed insemination failure in copulations between males and females of some Brazilian populations, including the Sobral siblings. Interestingly enough, Lu.…”
supporting
confidence: 90%
“…Mangabeira commented that the two forms were found in different ecological conditions and speculated that they might represent two species. The existence of a complex was confirmed by Ward et al (1983Ward et al ( , 1988 and Lanzaro et al (1993) in crossing experiments, although the male spot phenotype turned out to be only useful as a morphological marker of different species in some localities such as Sobral, CE (see below) (reviewed in Bauzer et al 2007).In Brazil, Lutzomyia longipalpis s. l. (Lutz & Neiva, 1912) is without any doubt the principal vector of American visceral leishmaniasis (AVL). It is present in nearly all of the foci of visceral leishmaniasis, is highly anthropophilic as well as readily feeding on dogs and foxes which act as reservoirs of Leishamania chagasi which are frequently found infected (reviewed in Lainson & Rangel 2005).…”
mentioning
confidence: 97%
“…Mangabeira (1962) was the first to suggest that this species might represent a species complex, based on differences in the number of pale spots on the male abdominal tergites. This hypothesis was later confirmed by crossbreeding studies (Ward et al, 1983;Lanzaro et al. 1993) and further supported by comparative analyses of pheromones (Ward et al 1988;Hamilton et al.…”
Section: Introductionmentioning
confidence: 79%
“…These parasites cause a wide spectrum of diseases, Leishmaniasis, which in the different visceral, cutaneous and mucocutaneous forms, can be fatal, disfiguring and debilitating if untreated. The WHO estimates that the global burden of disease expressed as DALYs (Disability AdjusArticle available at http://www.parasite-journal.org or http://dx.doi.org/10.1051/parasite/2008153252 geneous pattern of disease distribution as well as phenotypic and genotypic variation within L. longipalpis have led some researchers to conclude that L. longipalpis in Brazil is a species complex (Mangabeira, 1969;Ward et al, 1983;Conn & Mirabello, 2007;Maingon et al, 2008). However it is unclear how many members of the complex there are (Bauzer et al, 2007) although at least five have been suggested Bauzer et al, 2007).…”
mentioning
confidence: 99%
“…However it is unclear how many members of the complex there are (Bauzer et al, 2007) although at least five have been suggested Bauzer et al, 2007). The chemical ecology of L. longipalpis has received particular attention because sex pheromones produced by males appear to be good markers of members of the species complex (Ward et al, 1983;Hamilton et al, 2005;Watts et al, 2005) and because of the possibility that the sex pheromones may be used in more selective and efficient monitoring and/or control traps (Hamilton & Krishnakumari, 2004).…”
mentioning
confidence: 99%